Mia100 lubuskie - Pszczółkowski, Michał - red.; Mrówczyńska, Maria - wstęp; Abramiuk, Inna; Papaj, Wiktoria Maria; Ciesielska, Katarzyna; Keresztyen, Maria-Alexandra; Radzik, Tomasz; Kasishcheva, Yelyzaveta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The first volume of the Mia100 Lubuskie series, devoted to Zielona Góra, constitutes an interdisciplinary attempt to systematize and popularize the architectural heritage of one of the cities in the Lubusz region. Edited by Michał Pszczółkowski, the publication focuses on the presentation of one hundred selected architectural objects in Zielona Góra, highlighting their significance in both historical and contemporary contexts. The selection criteria are not limited to heritage value alone - the volume also includes industrial, public utility, residential, and sacral buildings, representing various periods and architectural styles.Each entry is accompanied by a concise description and a 3D visualization, making the book accessible to non-professional audiences as well.
Keywords: dziedzictwo architektoniczne; Lubuskie Region; interdyscyplinarne badania regionalne; Zielona Góra; architectural heritage; Lubusz Land; interdisciplinary regional studies